Optimasi Nilai Dakwah Yang Menyejukan Dalam Tardisi Budaya Lokal Sedekah Bumi Masyarakat Deroduwur Kabupaten Wonosobo - Moh. Amin; Robingun Suyud El Syam (Pusat Riset dan Inovasi Nasional, 2023)
The research seeks to reveal the optimization of the soothing value of da'wah in the local cultural tradition of almsgiving for the people of Deroduwur, Wonosobo Regency. The results of the study show that the procession of the Alms Earth ceremony contains soothing da'wah values ​​consisting of four values; divine values, the values ​​of social or community education, the values ​​of moral education, as well as the values ​​of respect and obedience to leaders. These values ​​are instilled by religious leaders so that people understand almsgiving as part of the essence of Islam which has positive values ​​and is important to preserve. The implications of this research are the importance of comprehensive understanding of religion so that it can be dialogued with local culture. Understanding the essence of religion in culture requires further research. Research contributes to Islamic building that is rahmatan lil 'alamin.